Response of the gut microbiota to changes in the nutritional status of red deer during winter - Jinhao Guo; Zheng Li; Xinxin Liu; Yongchao Jin; Yue Sun; Ziao Yuan; Weiqi Zhang; Jialong Wang; Minghai Zhang (Scientific Reports, 2024)
Abstract Unravelling abrupt alterations in the gut microbiota of wild species associated with nutritional stress is imperative but challenging for wildlife conservation. This study assessed the nutritional status of wild red deer during winter on the basis of changes in faecal nitrogen (FN) and urea nitrogen/creatinine (UN: C) levels and identified gut microbes associated with nutritional status via nutritional control experiments and metagenomic sequencing. The FN of wild red deer in winter 2022 was significantly lower than that in winter 2021 (p < 0.05, winter 2021: 1.37 ± 0.16% and winter 2022: 1.26 ± 0.22%), and the UN: C ratio increased (winter 2021: 2.19 ± 1.65 and winter 2022: 3.05 ± 3.50). Similar trends were found in late winter, which indicated greater nutritional pressure in winter (2022) and late winter. Compared with winter 2021, abundances of Ructibacterium and Butyrivibrio significantly increased, and Acetatifactor and Cuneatibacter significantly decreased during winter 2022 (p < 0.05). Compared with early winter, the cell growth and death pathways increased and lipid metabolism and its subpathway of secondary bile acid synthesis (ko00121) significantly decreased during late winter (p < 0.05), which was similar to the changes in malnourished experimental red deer. Abrupt alterations in the gut microbiota should receive increased attention when monitoring the nutritional health of wild ungulates. This study provides new insights and critical implications for the conservation of wild ungulate populations.